"KRITIK PENETAPAN HARGA IJARAH PADA GADAI EMAS (TINJAUAN FIKIH DAN ETIKA) " - Rinda Asytuti (Jurnal Hukum Islam, 2013)
Gold pawn financing at sharia banks rises when the price of gold The world is experiencing quite sharp fluctuations. This encourages society switching to gold investment. Starting from BRI Syariah, opening services gold pawning which is based on rahn and ijaroh contracts, but in practice opened a pawn buying service procedure which was allegedly vulnerable to speculation which is prohibited by the Islamic religion. The following pawn purchase product is known as This gold gardening is restricted by Bank Indonesia to limit movement customer speculation on gold. However, several sharia banks such as BNI and BSM, which also opens gold pawning services, does not carry out transactions buy a pawn like BRI sharia but only provides gold pawning services as in the DSN MUI fatwa No 26/DSN-MUI/III/2002. However The ongoing gold pawn transaction does not mean that it is without problems judging from jurisprudence and ethics, one of which is ijarah pricing which is based on method of tying and assessing the financing received. Ijaroh pricing determination and the gold pawning transaction was felt to have violated Rahn's conception It should be based on an urgent agreement which has the essence of ta'awun help help. For this reason, this article discusses the practice of pledging gold at banks Sharia and methods for determining ujroh on gold pawn products.